Comparison of balance performance of elite soccer players and skiers - Bayram, M.; Bayraktar, G.; Akyol, H.; Tozoglu, E. (International Journal of Sports Science, 2017)
This study aims to detect whether balance capability varies for elite soccer players and skiers. This study has been carried out by participation of 10 elite male athletes and 10 elite male athletes who are involved in active sports and do not have any health problem. The content of the study requires Warm- up and Stretching Exercises and, subsequently, the performance of One Leg Standing Test, One Legged Hop for Distance, Triple Legged Hop for Distance, Six-Meter Hop for Time, Cross Six-Meter Hop for Time and Flamingo Balance Tests. The analysis of some statistical data has been carried out by using the SPSS program version 13.0. The level of significance is specified as p < 0.05. It has been measured that the average of age, height, weight and years in active sports of the participants are respectively 23.35 ± 3.13, 175.95 ± 6.62, 72.35 ± 8.21, 10.55 ± 4.76. The one leg standing test has given the observation that the performance of the skiers are apparently superior to the footballers` performance. It is possible that the skiers have shown better performance since they usually use the lower extremities. In addition, despite the lack of observation of a difference in statistically significant level, a slight superiority on the skiers` side has been observed the values derived from the left-leg flamingo test, the right-leg standing test, the right-leg cross 6m hop for time and the left-leg cross 6m hop for time.